Synthesis and properties of polyimides containing hexaisobutyl-substituted T8 cages in their main chains. Issue 38 (29th March 2016) - Maegawa, T.; Miyashita, O.; Irie, Y.; Imoto, H.; Naka, K.
Abstract : We prepared two types of polyimides containing T8 cages in the main chains by polymerization of para -substituted bis(3-aminopropyl)hexaisobutyl-substituted T8 cage, and studied their mechanical, thermal, and optical properties. Abstract : Polymerization of a para -substituted bis(3-aminopropyl)hexaisobutyl-substituted T8 cage with pyromellitic dianhydride (PMDA) and 4, 4′-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) resulted in corresponding polyimides containing T8 cages in the main chains, denoted as T8 /PMDA polyimide and T8 /6FDA polyimide, respectively. The optical transmittance of the yellow-colored freestanding film of T8 /PMDA polyimide was over 90% in the visible region between 780 and 475 nm with a film thickness of 0.1 mm and the absorption edge was observed at approximately 590 nm. On the other hand, the film of T8 /6FDA polyimide showed excellent transparency in the visible region with an excellent optical transparency of over 90% even at 360 nm. DSC analysis of both the polyimides showed no glass transition and melt behavior between room temperature and 400 °C. Contact angles of water for the films of T8 /PMDA polyimide and T8 /6FDA polyimide were 97 ± 2° and 96 ± 5°, respectively, and both are significantly higher than that of poly(pyromellitic dianhydride-oxydianiline) (PMDA-ODA) polyimide and comparable to that of polyethylene. Martens' hardness and coefficient of thermal expansion (CTE) of T8 /PMDA polyimide were significantly lower and higher than that of PMDA-ODA polyimide, respectively, and these values are comparable to those of polyethylene. The replacement of PMDA with 6FDA significantly improved Martens' hardness and CTE. The XRD analysis for the T8 -containing polyimides indicates a highly packed nanostructure of the hexaisobutyl-T8 unit in the polymer films and the isobutyl-T8 unit in T8 /6FDA polyimide has a more packed structure than that in T8 /PMDA polyimide.